Understanding Bank Recovery and Resolution in the EU : A Guidebook to the BRRD - World Bank Group (World Bank, Vienna, 2017)
The 2007 financial crisis has exposed major weaknesses in global financial systems, including the threat to financial stability posed by banks that were too big, interconnected and complex to be closed or go bankrupt. As a result, many banks have been rescued using public support, allowing for an uninterrupted provision of their services, but effectively shifting (most) of their losses to taxpayers instead of banks’ owners or investors. The political realities following the bail-out of banks called for game-changing regulation to reduce both the likelihood and the impact of failure.The Banking Recovery and Resolution Directive (BRRD) became one of the most important building blocks of the Banking Union. The BRRD is the outcome of a long negotiation process. The new bank recovery and resolution framework has wide reaching implications, both within the EU but also for countries with banking relationships with the EU. This Guidebook aims to explain the scope, the principles, and the rationale of the BRRD and related secondary legislation and guidance. Expert contributors, including lawyers and academics, share in this Guidebook their experience of and insights to the BRRD negotiation process, recovery and resolution planning, adoption of resolution decisions and the negotiation of bail-in. The Guidebook also raises awareness of discretionary or non-regulated areas and provides some initial thoughts for further development and possible implementation challenges. These challenges include but are not limited to the management of potential conflict of interests, the application of the public interest test, the choice of resolution tools, and the interaction between cross-border regulations. The Guidebook, together with the accompanying case studies, should help FinSAC client countries understand the resolution process and identify the impact that the BRRD will have on their own financial systems.